Platelet count and platelet indices in patients of pregnancy-induced hypertension at a rural tertiary care hospital in western India - Nagare Mangala; Alisha Shaikh; Harsha Dangare (Journal of Pathology of Nepal)
Background: Pregnancy-induced hypertension is a serious complication during pregnancy causing maternal and fetal morbidity and mortality. Pregnancy-induced hypertension associated with thrombocytopenia can help in predicting the severity of the disease. The study aimed to study the platelet count, and platelet indices in Pregnancy induced hypertension patients and compare them with normotensive pregnant women.